Support provided by outreach team leaders to caregivers of HIV/AIDS orphans in the North-West province of South Africa - Boitumelo Joy Molato; Salaminah S. Moloko-Phiri; Magdalena P. Koen; Molekodi J. Matsipane (BMC, 2024)
Abstract Background The human immunodeficiency virus (HIV) and acquired immunodeficiency deficiency syndrome (AIDS) epidemic have left an overwhelming impact on communities worldwide, particularly in Sub-Saharan Africa, where its effects on family structures are particularly pronounced. Caregivers of HIV/AIDS orphans encounter challenges in fulfilling their caring duties. Consequently, they rely on the outreach team leaders (OTLs) for support to care for HIV/AIDS orphans. Aim This study aimed to explore and describe support provided by OTLs to caregivers of HIV/AIDS orphans in the North West Province of South Africa. Methods The exploratory, descriptive, and contextual design meaning the study was conducted was in the contexts where caregivers of HIV/AIDS orphans reside. The study was conducted in five local municipalities in the Ngaka Modiri Molema district of the North West Province of South Africa. Ward-based outreach nurses were participants in the study. Semi-structured focus group interviews were used for data collection. Thematic analysis was used to analyze data. Throughout the study, ethical principles were adhered to. The study also adhered to four trustworthiness principles: credibility, confirmability, transferability, and dependability. Results Three main themes emerged from this study: the conduction of home visits to caregivers of HIV/AIDS orphans, the coordination of a multidisciplinary team for support, and the facilitation of support groups. Conclusions This study revealed that that caregivers of children orphaned by HIV/AIDS benefitted from the support provided by OTLs in the North West province of South Africa. The support provided by OTLs harnessed positive relationship between caregivers and children orphaned by HIV/AIDS.